PENGARUH DIMENSI KUALITAS PELAYANAN JASA SERVIS TERHADAP KEPUASAN KONSUMEN (Studi pada PT. Kartika Sari Mulia – Toyota Authorized, Malang) - Ramadhani, Pristia Hanum; Djazuli, Atim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The research aims to describe and analyze the influence of the dimentions of service quality on customer satisfaction at car servicing service in automotive company PT. Kartika Sari Mulia – Toyota Authorized, Malang. This type of the research is an explanatory research with quantitative approach. Type of the data used in this research are primer data, with 90 sample of visitors workshop in Toyota Kartika Sari, where the method does not use population qualification. The research variables namely; the independent variable is Physical Evidence, Reliability, Responsiveness, Assurance and Empathy. Customer Satisfaction as well as the dependent variable. This study was conducted using multiple linear regression. It can be seen the influence of Physical Evidence, Responsiveness, Assurance and Empathy towards Customer Satisfaction significantly, whereas there is no influence Reliability significantly to Customer Satisfaction. Keywords: Physical Evidence, Reliability, Responsiveness, Assurance, Empathy, Customer Satisfaction